P2X3 receptor‐mediated visceral hyperalgesia and neuronal sensitization following exposure to PTSD‐like stress in the dorsal root ganglia of rats. Issue 3 (25th October 2016) - He, Y.‐Q.; Lang, X.‐Q.; Lin, L.; Ji, L.; Yuan, X.‐Y.; Chen, Q.; Ran, Y.‐M.; Chen, H.‐S.; Li, L.; Wang, J.‐M.; Wang, Z.‐G.; Gregersen, H.; et al.
Abstract: Background: Patients with posttraumatic stress disorder (PTSD) often share co‐morbidity with chronic pain conditions. Recent studies suggest a role of P2X3 receptors and ATP signaling in pain conditions. However, the underlying mechanisms of visceral hyperalgesia following exposure to PTSD‐like stress conditions remain unclarified. Methods: The behavior and hormones relevant for PTSD were studied. Visceromotor responses (VMR) and the abdominal withdrawal reflexes (AWR) to colorectal distention (CRD) were recorded to determine P2X3‐receptor–mediated alteration of hyperalgesia following single‐prolonged stress (SPS) exposure. Immunofluorescence, Western blotting, and patch‐clamp were used. Key Results: The escape latency, adrenocorticotropic hormone and cortisol were increased on days 7–14. Visceromotor responses and AWR was reduced at day 1 in SPS rats but increased to higher levels than in controls after exposure to day 7. Intrathecal administration of the P2X3‐receptor antagonist TNP‐ATP abolished the CRD response. Based on immunofluorescence and Western blotting analysis, SPS‐treated rats exhibited reduced P2X3 expression in dorsal root ganglia (DRG) after day 1 compared with controls. P2X3 expression in DRG was enhanced on day 7 after SPS and the increase of the P2X3 expression was maintained on day 14 and 21 compared with controls. The P2X3‐receptor agonist α, β‐me ATP (10 μM) induced a fast desensitizing inward current in DRG neurons of both control and SPS‐treated rats. The average peak current densities in SPS‐treated group were increased 3.6‐fold. TNP‐ATP (100 nM) markedly blocked all fast α, β‐me ATP‐induced inward currents in the DRG neurons both in control and SPS‐treated rats. Conclusions & Inferences: The data indicate an important role of P2X3 signaling in visceral hyperalgesia following PTSD‐like stress. Abstract : Patients with posttraumatic stress disorder share co‐morbidity with chronic pain conditions. The purpose was to study the underlying mechanisms of increased pain sensitivity in rats following exposure to posttraumatic stress disorder conditions. Motoric responses to colorectal distention were reduced initially in stress‐exposed rats but increased afterwards to higher levels. Stress‐exposure initially exhibited reduced dorsal root ganglion P2X3 ionic channel expression, which was followed by increased P2X3 expression. The data indicate an important role of P2X3 signaling in visceral pain.